Mothers’ Experiences in Implementing Responsive Feeding for Stunted Toddlers: A Qualitative Phenomenological Study - Julianti, Erna; Elni, Elni; Azmy, Restu Amalia; Zamziri, Zamziri (Chakra Brahmanda Lentera Institute, 2025)
Background: Reducing stunting rates is a priority for health programs in Indonesia, including in Bangka Belitung. One of the factors of stunting is a responsive feeding problem. The problems experienced by mothers related to responsive feeding are that the way of feeding according to age is not optimal, does not provide examples of healthy eating habits, does not encourage children to eat, and does not interact with children when eating, because they are busy with household chores. Methods: The research used a descriptive phenomenological approach, and the ethical considerations in the study were beneficence, justice, and Respect for human dignity. The research participants involved were five mothers having stunting children, because saturation (data saturation) was achieved during data collection, so that no new information was obtained. The sample was selected using a purposive sampling technique. Inclusion criteria included mothers with stunting toddlers who could express their experiences and spoke Indonesian. Researchers also conducted in-depth interviews to collect data. Researchers used COREQ as a guideline. The data were analyzed using the Colaizzi method. Results: This research discovered five themes, including children's independence in eating versus being fed, refusal to eat, interaction between parents and children when eating, knowing signs of hunger and fullness in children, and eating texture according to the child's age. Conclusion: Eventually, it is expected that mothers can apply responsive feeding and use it as a nursing intervention to improve children's eating habits and abilities more optimally.